Exercise as a Therapeutic Intervention in Gestational Diabetes Mellitus: A Narrative Review of Clinical Outcomes and Glycemic Control - Kołodziejczyk, Julia; Pietrzak, Maria; Łupina-Romaniuk, Marcela; Chawryło, Aneta; Pietraś, Paulina; Piecuch, Dominika; Oleksińska, Karolina; Świetlicka, Gabriela; Stolarczyk, Michał; Pracoń, Karolina (Quality in Sport, 2026)
Background: Gestational diabetes mellitus (GDM) is one of the most common metabolic complications of pregnancy and is associated with adverse maternal and neonatal outcomes. Lifestyle modification remains the cornerstone of treatment, with increasing attention directed toward the therapeutic role of physical activity. Aim: This narrative review aimed to evaluate the impact of exercise as a therapeutic intervention on glycemic control and clinical outcomes in women with GDM. Material and Methods: A literature search was conducted using the PubMed database, including studies published from 2021 onwards. The review focused on randomized controlled trials, systematic reviews, and meta-analyses investigating the effects of physical activity on glycemic control, insulin therapy, and maternal and neonatal outcomes in GDM. Results: Available evidence suggests that regular physical activity improves glycemic control in women with GDM, particularly by reducing postprandial glucose levels. Exercise may also decrease the need for insulin therapy and contribute to improved maternal outcomes, including reduced excessive gestational weight gain. Additionally, physical activity appears to lower the risk of macrosomia and other selected neonatal complications. The effectiveness of exercise interventions depends on their type, intensity, timing, and, importantly, adherence. Conclusions: Exercise represents a safe and effective adjunct in the management of gestational diabetes mellitus. However, its clinical impact is influenced not only by physiological effects but also by practical factors such as feasibility and long-term adherence. Individualized and structured exercise recommendations may enhance the therapeutic potential of physical activity in GDM.